2021
DOI: 10.1002/pls2.10052
|View full text |Cite
|
Sign up to set email alerts
|

Impact responses of an open‐cell natural rubber foam impregnated with shear thickening fluid

Abstract: This research aims to investigate the impact responses of an impact absorbing material prepared from natural rubber (NR). Shear thickening fluid (STF) was developed in order to improve compatibility, and impact response capability of a NR foam. The material was prepared by impregnating NR foam with STF (30 wt% nanosilica with 10 nm). The obtained material is soft under normal circumstances, but immediately stiff when undergoing sudden impact before softening again. The effects of foam densities (0.098, 0.15, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Scientific evidences showed that protective liners combined with non-Newtonian fluids provided increased control in energy dissipation over several impacts (Spinelli et al, 2018), mitigating pressure of collision and impulse compared to standard foamed liners (Mears, 2019). In some cases STSs can even improve the impact responses of materials providing comparable results with commercial available products (e.g., kneepads) with dilatant behavior (Kaewpradit, 2021). Regarding face protection, a dental appliance has been also reported to protect users against injury from impacts occurring in sports and other leisure activities responsible for teeth damages.…”
Section: Use Of Stss In Sport Productsmentioning
confidence: 99%
“…Scientific evidences showed that protective liners combined with non-Newtonian fluids provided increased control in energy dissipation over several impacts (Spinelli et al, 2018), mitigating pressure of collision and impulse compared to standard foamed liners (Mears, 2019). In some cases STSs can even improve the impact responses of materials providing comparable results with commercial available products (e.g., kneepads) with dilatant behavior (Kaewpradit, 2021). Regarding face protection, a dental appliance has been also reported to protect users against injury from impacts occurring in sports and other leisure activities responsible for teeth damages.…”
Section: Use Of Stss In Sport Productsmentioning
confidence: 99%
“…STF is a dense colloidal suspension with a rapid increase in viscosity at high shear rates. [12][13][14] The excellent material properties of STF have led to a wide range of applications in many fields, such as human body protection, [15][16][17] vibration damping and energy absorption, [18][19][20][21][22] and surface polishing. 23,24 Many studies have shown that the impact resistance of fabrics is greatly improved after treating high-performance fabrics with STF.…”
Section: Introductionmentioning
confidence: 99%
“…One of the recently most widely discussed technology that has demonstrated ability to improve ballistic resistance in soft body armor design studies is liquid body armor technology, which involves the impregnation of high-performance fiber-based fabrics with a shear thickening fluid (STF). [34][35][36][37][38] Research efforts are therefore underway to develop different designs to improve the energy absorption capacity of para-aramid fabrics through interply/intraply hybridization with different types of synthetic and natural fibers, layering of different materials or matrices and impregnation with STF, micro/nano-particles or the combination of these. [39][40][41] However, the contribution of polymer-based nanofiber mats to the ballistic impact response of the textile laminated armor system has not yet been reported in the open literature, despite the promising improvement in the mechanical properties of composites with a very small nanofiber reinforcement (<10 wt%) due to their extremely high surface area/mass ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Yahaya et al, 33 hybrid composite laminates consisting of natural kenaf fibers and Kevlar fabrics were developed, and it was found that the integration of nonwoven kenaf layers into the composite structure results in a positive effect in terms of V50 ballistic limit and energy absorption capability. One of the recently most widely discussed technology that has demonstrated ability to improve ballistic resistance in soft body armor design studies is liquid body armor technology, which involves the impregnation of high‐performance fiber‐based fabrics with a shear thickening fluid (STF) 34–38 …”
Section: Introductionmentioning
confidence: 99%